(Re) configuração do espiritismo kardecista no Recife e suas interfaces com a tradição católica e as religiões indígenas e afro-brasileiras - Queiroz, Eroflim João de (2017)
The present study is related to the Master of Science of Religion, to the line of research: Brazilian religious field, culture and society, with the purpose of investigating in the Catholic religion and in Afro-Brazilian traditions the elements redefined by the Kardecist doctrine for its configuration in the Recife. For this study, we use as base the Human and Social Sciences, specifically History, Sociology, Anthropology and, in particular, the Sciences of Religion. From the methodological point of view, the research is characterized by the qualitative nature, in which the information is collected through historical research and in the empirical field, semistructured research, formed by interviews with 10 mediums who work in Spiritist Centers of the city of Recife. The theoretical framework adopted is anchored in the analysis of authors such as Canclini (2009, 2015), Hall (2003, 2011 and 2014), Silva (2014) and others dealing with the understanding of cultural hybridity and identity. In addition, the history of Spiritism is analyzed, where we highlight Sá (2001) and Maior (2002 and 2006), as well as, primary sources, the books that compose the Kardecist codification. In the analysis of the interviews, we used the technique of content analysis for our study. We find through these interviews the assertion that the communicating spirits in the mediumistic meetings belong to diverse religious traditions existing in Brazil, especially those of Afro-Brazilian traditions, and that in these Centers they manifest freely, in their cultural and religious identities, with respect to the only restrictions to rituals exist. Thus, the results of the research reveal the influence of religious hybridity on the (re) configuration of spiritualism in Recife. In this way we hope to contribute to the understanding of the religious hybridism that has been established since the arrival of these religions in Brazil and the (re) configuration of Kardecista spiritualism in Recife and its interfaces with the Catholic religion, indigenous religious traditions and Afro-Brazilian religions.